1989
DOI: 10.2136/sssaj1989.03615995005300030018x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Humic Acid from No‐Tilled and Tilled Soils Using Carbon‐13 Nuclear Magnetic Resonance

Abstract: Chemical composition of humic acids is important due to their reactivity with soil‐applied pesticides and fertilizer amendments. Humic acids from continuously (7 yr) no‐tilled and tilled cotton, corn, and soybean plots in West Tennessee were characterized by 13C‐NMR from soils sampled at various depths. Humic acids were extracted with dilute NaOH solution and purified with KOH‐KCL and HCL‐HF solution, respectively. NMR solution spectra generated on a Jeol FX 90Q spectrometer (Jeol Co., Tokyo, Japan) were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 0 publications
2
3
0
1
Order By: Relevance
“…Differences between cropping systems are observed far less in the HS spectra than in spectra of whole soil samples, in agreement with the smaller differences in their C and N concentrations (Table 1). This is also in line with results of Stearman et al (1989) who reported only minor effects of tillage on humic acid structures by 13C NMR, irrespective of clear differences in the Corg concentrations of whole soils.…”
Section: Extracted Humic Substances (Hs)supporting
confidence: 92%
“…Differences between cropping systems are observed far less in the HS spectra than in spectra of whole soil samples, in agreement with the smaller differences in their C and N concentrations (Table 1). This is also in line with results of Stearman et al (1989) who reported only minor effects of tillage on humic acid structures by 13C NMR, irrespective of clear differences in the Corg concentrations of whole soils.…”
Section: Extracted Humic Substances (Hs)supporting
confidence: 92%
“…and aliphatic C (0-110 ppm). Other studies have reported similar findings (Stearman et al 1989;Arshad et al 1990;Dieckow et al 2009). The average accumulation of alkyl C under NTS (24.1%) and CTS (20.4%) relative to CT (16.2%) across the two soil layers may be attributable mainly by a selective preservation and an in situ synthesis of carbon (Sollins et al 1996;Baldock and Skjemstad 2000).…”
Section: Effects Of Tillage On the Composition Of Socsupporting
confidence: 65%
“…Tillage management affects the distribution of SOC and its chemical composition (Bayer et al 2002;Ding et al 2002;Du et al 2010;Zhao et al 2012;Piccoli et al 2016). The concentration of SOM in conventional tillage (e.g., moldboard plow) soils is often associated with a decrease in aliphatic C, and an increase in aromatic and carbonyl C and concentrations of semi-quinone free radicals (Stearman et al 1989;Bayer et al 2000), leading to greater SOM humification. In contrast, conservation tillage usually enhances accumulation of surface SOM as reflected by higher stratification ratios (SRs) (Sá and Lal 2009;Du et al 2010), which was defined by Franzluebbers (2002) as the value of quotient in the SOC at the surface and deeper layers.…”
Section: Introductionmentioning
confidence: 99%
“…The freeze-dried humic fractions were subjected to solid state 13 C NMR analysis on a Bruker DSX 400 with cross polarization and magic-angle spinning (CPMAS), proton decoupling with contact time 2.00 ms, recycle time 5.00 s, spectral width 20000.0 Hz, spinning speed 3500 Hz, number of scans 6000, spectrometer frequency 50.330 MHz, and acquisition time 51.25 ms. According to the method recommended by Wilson (1981), Wershaw (1985), and Stearman et al (1989), the range of chemical shift of 0-190 ppm of the solid state CPMAS 13 C NMR spectra were divided into the ranges of 0-50, 50-90, 90-110, 110-140, 140-160, and 160-190 ppm. The areas covered by the spectra in these ranges were used to estimate the distribution percentages of characteristic carbons in the various samples.…”
Section: Characterization Of Som and Humic Substance Fractionsmentioning
confidence: 99%